Selective Inhibition of 11β-Hydroxysteroid Dehydrogenase Type 1 Attenuates High-Fat Diet-Induced Hepatic Steatosis in Mice - Li H; Sheng J; Wang J; Gao H; Yu J; Ding G; Ding N; He W; Zha J (Dove Medical Press, 2021)
Huashan Li,1,* Jianying Sheng,1,* Jing Wang,1 Haiting Gao,1 Jing Yu,2 Guoxian Ding,2 Ning Ding,1 Weiqi He,1,3 Juanmin Zha1 1Jiangsu Key Laboratory of Neuropsychiatric Diseases and Cambridge-Suda (CAM-SU) Genomic Resource Center, Medical College of Soochow University, Department of Oncology, The First Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China; 2Department of Geriatrics, Division of Geriatric Endocrinology, The First Affiliated Hospital to Nanjing Medical University, Nanjing, People’s Republic of China; 3State Key Laboratory of Pharmaceutical Biotechnology, Nanjing University, Nanjing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weiqi He; Juanmin ZhaCambridge-Suda (CAM-SU) Genomic Resource Center, Medical College of Soochow University, Department of Oncology, The First Affiliated Hospital of Soochow University, 199 Ren-Ai Road, Suzhou, 205123, People’s Republic of ChinaTel +86-512-6588-3545Fax +86-6588-3562Email whe@suda.edu.cn; zhajuanmin@suda.edu.cnIntroduction: The effect of 11β-hydroxysteroid dehydrogenase type1 (11β-HSD1) inhibition on hepatic steatosis is incompletely understood. Here, we aimed to determine the therapeutic effect of BVT.2733, a selective 11β-HSD1 inhibitor, on hepatic steatosis.Materials and Methods: C57B/6J mice were randomly divided into a low-fat diet (LFD) fed group and a high-fat diet (HFD) fed group. Mice were fed with HFD for 28 weeks which induced obesity and severe hepatic steatosis. The two groups were further divided into four groups as follows: LFD, LFD with BVT.2733, HFD, and HFD with BVT.2733. Mice in LFD+BVT and HFD+BVT groups were intraperitoneally injected with BVT.2733 daily for 30 days. Effects of BVT.2733 on mice body weight, serum lipid profile, serum free fatty acids (FFAs), glucocorticoid levels, gene expression in adipose and liver tissues were assessed.Results: Injection of a low dose of BVT.2733 (50 mg/kg/day) reduced body weight and hyperlipidemia, but did not improve glucose tolerance and insulin resistance in diet-induced obese mice. The low dose of BVT.2733 attenuated hepatic steatosis, liver injury, and liver lipolytic gene expression in diet-induced obese mice. Besides, the low dose of BVT.2733 reduced fat mass and lipolysis in visceral adipose tissues, hepatic FFAs, and serum corticosterone levels in diet-induced obese mice.Conclusion: Our study shows that moderate inhibition of 11β-HSD1 by BVT.2733 reduces FFAs and corticosterone synthesis in fatty tissues, thereby attenuates the delivery of corticosterone and FFAs to the liver. Collectively, this prevents high-fat diet-induced hepatic steatosis.Keywords: 11β-HSD1, hepatic steatosis, inhibitor, adipose tissue, free fatty acids